The Effect of Ball Feeling Training on Dribbling Ability in SSB Esa Pratama Players, Kerinci Regency (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the effect of ball feeling training on dribbling ability in SSB Esa Pratama players, Kerinci Regency. This research is a quasi-experimental study using a "One Group Pretest-Posttest Design". The study was conducted for 16 sessions with 3 meetings per week at the Trides football field, Tebing Tinggi, Kerinci Regency. The population consisted of 40 SSB Esa Pratama players, and the sample was selected using a purposive sampling technique with 18 players meeting the criteria (aged 10-13 years, willing to participate in 16 training sessions, registered as SSB Esa Pratama students, and all male). The instrument used was a dribbling ability test. The results showed a significant effect of ball feeling training on dribbling ability. Before training, the pretest mean was 22.37 seconds, and after training, the posttest mean was 19.57 seconds. The standard deviation for the pretest was 2.678, and the posttest was 2.528. The minimum pretest time was 18 seconds, with a maximum of 27 seconds, while the posttest minimum time was 15 seconds, with a maximum of 25 seconds. Statistical analysis showed t-calculated (16.415) > t-table (2.110). Ball feeling training effectively improves dribbling skills in young football players and should be integrated into regular training programs. This study includes 25 references, 10 tables, 2 figures, and training program documentation as supplemental materials.